2009
DOI: 10.1111/j.1755-0998.2008.02392.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing statistical power of SNPs for population structure and conservation studies

Abstract: Single nucleotide polymorphisms (SNPs) have been proposed by some as the new frontier for population studies, and several papers have presented theoretical and empirical evidence reporting the advantages and limitations of SNPs. As a practical matter, however, it remains unclear how many SNP markers will be required or what the optimal characteristics of those markers should be in order to obtain sufficient statistical power to detect different levels of population differentiation. We use a hypothetical case t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
238
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(249 citation statements)
references
References 41 publications
(84 reference statements)
10
238
0
1
Order By: Relevance
“…Significant linkage disequilibrium (P \ 0.05) was observed only for pairs of SNPs originating from the same EST sequence. The latter further increased expectations of diminished statistical power compared to the microsatellites but results of Morin et al (2009) demonstrated that although linked loci reduce the coverage of the genome, the statistical power of SNPs for population structure can actually be increased by including multiple SNPs within loci and inferring haplotypes rather than using only unlinked loci. In this study, the very small number of haplotypes inferred with PHASE was unlikely to have resulted in a significant gain in statistical power.…”
Section: Resultsmentioning
confidence: 99%
“…Significant linkage disequilibrium (P \ 0.05) was observed only for pairs of SNPs originating from the same EST sequence. The latter further increased expectations of diminished statistical power compared to the microsatellites but results of Morin et al (2009) demonstrated that although linked loci reduce the coverage of the genome, the statistical power of SNPs for population structure can actually be increased by including multiple SNPs within loci and inferring haplotypes rather than using only unlinked loci. In this study, the very small number of haplotypes inferred with PHASE was unlikely to have resulted in a significant gain in statistical power.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that four to twelve times more SNPs are needed for population structure inference to match the statistical power of one microsatellite (Liu et al, 2005). For highly dispersive organisms it has been shown that the detection of low levels of differentiation is possible with a minimum of 80 SNPs (Morin et al, 2009;Ryman et al, 2006). Our large set of hundreds of SNPs should thus allow to scale the genetic marker system to the needs of future studies of the interaction between landscape features and microevolutionary processes (Manel et al, 2003).…”
Section: Utility Of Snps In African Buffalomentioning
confidence: 99%
“…Recent technological advances have revolutionized the generation of these genetic resources, allowing DNA-library construction, large-scale sequencing and identification of single nucleotide polymorphism (SNP) genetic markers (Seeb et al, 2011). SNPs were shown to constitute highly informative markers (Morin et al, 2009) and lead to a better inference of population structure than microsatellites (Liu et al, 2005;Santure et al, 2010). Attention has begun to shift toward SNPs as preferred genetic markers due to their increased power of resolution and accuracy for studying fine scale population structure (Schlötterer, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Nussberger et al (2013) developed a diagnostic marker set containing 48 SNPs that allows the identification of wildcats, domestic cats, their hybrids and backcrosses, and have demonstrated their accurate genotyping in single hairs (Nussberger et al, 2014). However, these authors used a restricted set of reference Toward a genome-wide approach for detecting hybrids R Oliveira et al samples, and the choice of highly differentiated traits/loci from a small panel of parental individuals has been considered to possibly overlook population differentiation (Brumfield et al, 2003;Schlötterer, 2004;Morin et al, 2009). This is a concern among European wildcat populations because the genetic partition of the populations is still poorly known, and central European wildcats might not be as fragmented as other regions (Mattucci et al, unpublished).…”
Section: Bayesian Clusteringmentioning
confidence: 99%
“…Although microsatellites have been the dominant markers in wildcat genetic studies (for example, Beaumont et al, 2001;Randi et al, 2001;Pierpaoli et al, 2003;Lecis et al, 2006;Germain et al, 2008;Eckert et al, 2010;O'Brien et al, 2009), and recently mtDNA diagnostic SNPs have been suggested (Driscoll et al, 2011), the increasing availability and numerous advantages of nuclear SNPs make them an appealing alternative and/or a complement to maternal and paternal lineage markers. SNPs have been attracting a growing interest in a wide range of evolutionary applications and are becoming efficient tools among wildlife conservation-oriented studies (Brumfield et al, 2003;Morin et al, 2004;Seddon et al, 2005;Morin et al, 2009). Offering less variability per locus than STRs, SNPs provide a substantial number of advantages, namely: (i) reduced propensity for homoplasy due to lower mutation rates; (ii) higher density and more uniform distribution in genomes; (iii) suitability for successful high-throughput genotyping and straightforward comparability and transportability across laboratories and detection protocols; and (iv) highly successful application in fragmented DNA samples, for example, noninvasive and historical DNA (see Brumfield et al, 2003;Morin et al, 2004;Garvin et al, 2010 for reviews).…”
Section: Snp Simulations For Admixture Analysismentioning
confidence: 99%